Best Horror of the Year, Volume sixteen - Datlow, Ellen; Barb, Patrick; Campbell, Ramsey, 1946-; Cluley, Ray; Due, Tananarive, 1966-; Evenson, Brian, 1966-; Golden, Christopher; Grant, Helen, 1964-; Hirshberg, Glen, 1966-; Holmes, Carly; Hook, Andrew; Hughes, Charlie; et al. (Night Shade Books, 2024)
"For more than four decades, Ellen Datlow has been at the center of horror. Bringing you the most frightening and terrifying stories, Datlow always has her finger on the pulse of what horror readers crave. Now, with the sixteenth volume of the series, Datlow is back again to bring you the stories that will keep you up at night. Encompassed in the pages of The Best Horror of the Year have been such illustrious writers as: Neil Gaiman, Stephen King, Stephen Graham Jones, Joyce Carol Oates, Laird Barron, Mira Grant, and many others. With each passing year, science, technology, and the march of time shine light into the craggy corners of the universe, making the fears of an earlier generation seem quaint. But this light creates its own shadows. The Best Horror of the Year chronicles these shifting shadows. It is a catalog of terror, fear, and unpleasantness as articulated by today's most challenging and exciting writers." --